AB0474 Comparison of drug retention rates between anti-tumor necrosis factor agents in rheumatoid arthritis and ankylosing spondylitis in daily clinical practice. (23rd January 2014) - Senabre-Gallego, J.M.; Rosas, J.; Santos-Soler, G.; Santos-Ramírez, C.; Sánchez-Barrioluengo, M.; Barber, X.; Salas-Heredia, E.; Cano, C.; Llahí, N.
Abstract : Background: The efficacy of different anti-tumor necrosis factor alpha (anti-TNF) agents in rheumatoid arthritis (RA) and ankylosing spondylitis (AS) has not been directly compared in clinical trials, and meta-analysis showed no differences between them 1, 2 . Drug retention rates obtained in observational studies are indicators of treatment success 3 . Objectives: To analyze the retention rates and causes of discontinuation among anti-TNF agents in our local cohort of RA and AS patients. Methods: We conducted an observational prospective study. Patients treated with infliximab (INF), etanercept (ETN) and adalimumab (ADA) since January 2001 to November 2011 were included. The causes of discontinuation were categorized as: inefficacy, adverse events, clinical remission and loss of follow up. Kaplan-Meier survival function was estimated. Factors that could determine the time to discontinuation were analyzed using a Cox proportional hazard ratio model. Results: A total of 318 treatments were started: 97 INF, 105 ETN and 116 ADA. Total exposure to TNF inhibitors was 589 patient-years. Discontinuations due to adverse events were: 49% INF, 34% ADA and 33% ETN. ETN retention curves were higher than INF or ADA. Cox regression analysis showed higher risk of discontinuation for INF than ETN (Table 1 ) in both RA and AS patients, but comparison between ETN and ADA do not showed statistical differences. Conclusions: ETN estimated retention curves were higher than INF or ADA. The risk of INF discontinuation is more than double compared with ETN in both RA and AS. Comparison between ETN and ADA do not showed statistically significant differences. References: Gartlehner G, Hansen RA, Jonas BL, Thieda P, Lohr KN. The comparative efficacy and safety of biologics for the treatment of rheumatoid arthritis: a systematic review and metaanalysis. J Rheumatol. 2006;33:2398–408. McLeod C, Bagust A, Boland A, Dagenais P, Dickson R, Dundar Y, et al. Adalimumab, etanercept and infliximab for the treatment of ankylosing spondylitis: a systematic review and economic evaluation. Health Technol Assess. 2007;11:1–158, iii-iv. Wolfe F. The epidemiology of drug treatment failure in rheumatoid arthritis. Baillieres Clin Rheumatol 1995;9:619–32. Disclosure of Interest: J. Senabre-Gallego Grant/Research support from: Asociaciόn para la Investigaciόn en Reumatología Marina Baixa (AIRE-MB), J. Rosas: None Declared, G. Santos-Soler: None Declared, C. Santos-Ramírez: None Declared, M. Sánchez-Barrioluengo: None Declared, X. Barber: None Declared, E. Salas-Heredia: None Declared, C. Cano: None Declared, N. Llahí: None Declared